2022
DOI: 10.1007/s11701-021-01354-w
|View full text |Cite
|
Sign up to set email alerts
|

Virtual postoperative visits following robotic gynecologic surgery: a study of patient satisfaction, safety, and feasibility

Abstract: Since the onset of the COVID-19 pandemic the use of telehealth has burgeoned. Numerous surgical specialties have already adopted the use of virtual postoperative visits, but there is data lacking in both robotics and gynecology. In this single-institution prospective cohort study we sought to evaluate the patient satisfaction, feasibility and safety of postoperative telehealth visits following robotic gynecologic surgery. Thirty-three patients undergoing robotic gynecologic procedures participated in a postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…With the widespread adoption of telemedicine during the COVID-19 pandemic, some minimally invasive gynecologic surgeons transitioned postoperative visits to telemedicine [22]. A prospective cohort study of 33 patients who had robotic gynecologic surgeries showed high patient satisfaction with a 2-week postoperative video virtual visit rather than an office visit [23 ▪ ]. Although the study was not powered to assess broad feasibility or safety, only two patients required an in-person visit for complications.…”
Section: Postoperative Visitsmentioning
confidence: 99%
“…With the widespread adoption of telemedicine during the COVID-19 pandemic, some minimally invasive gynecologic surgeons transitioned postoperative visits to telemedicine [22]. A prospective cohort study of 33 patients who had robotic gynecologic surgeries showed high patient satisfaction with a 2-week postoperative video virtual visit rather than an office visit [23 ▪ ]. Although the study was not powered to assess broad feasibility or safety, only two patients required an in-person visit for complications.…”
Section: Postoperative Visitsmentioning
confidence: 99%